Materia laboral N° 00269-2012-0-1903-JR-CA-01. Demandante: Miriam Elizabeth Cárdenas Romero de Solano. Demandado: Dirección Regional de Salud y otros. Materia: nulidad de resolución o acto administrativo. Órgano jurisdiccional: Juzgado de Trabajo Transitorio de Maynas / Materia constitucional N° 00374-2011-0-1903-JR-CI-02. Demandante: Teddy Pinedo Arcentales. Demandado: Municipalidad Provincial de Maynas. Materia: acción de amparo. Órgano jurisdiccional: 2° Juzgado Civil – sede central - Cobos Montalvan, Andrea Roxana (2021)
The present work of professional sufficiency deals with the work carried out in the Public Ministry, from December 1, 2017 to date, in the condition of Law and Political Sciences Graduate of the UNIVERSIDAD NACIONAL DE LA AMAZONIA PERUANA, who to opt who to opt for the title of Lawyer through the modality of Professional Sufficiency – Support of Files, will describe in this work the application of the knowledge learned in the exercise of the functions as Assistant in Fiscal Function respectively, tasks carried out for a period of more than three years, justifying professional sufficiency. In addition two summaries of judicial files will be presented, one on constitutional matters and the other on labor matters, which will be exposed to the authorizing jury to obtain the respective professional title, a file that All contain all the procedural acts carried out to resolve the particular case.